Allergen Component Specific IgE Measurement With the Immulite™ 2000 System: Diagnostic Accuracy and Intermethod Comparison. Issue 2 (5th May 2014) - Villalta, Danilo; Da Re, Mirella; Conte, Mariaelisabetta; Martelli, Paola; Uasuf, Carina Gabriela; Barrale, Maria; Chiusa, Stella Maria La; Brusca, Ignazio
<x xml:space="preserve">Abstract</x> Background The identification of the allergenic molecules, associated to the advances in the field of recombinant allergens, led to the development of a new concept in allergy diagnosis called component‐resolved diagnosis. The aim of our study was to evaluate the diagnostic accuracy of different allergen components using the full automatic singleplex quantitative platform Immulite™ 2000. Methods One hundred ninety‐five allergic outpatients (35 to olive pollen, 35 to birch pollen, 35 to profilin, 35 to house dust mites, 35 to peach, and 20 to shrimp) and 20 negative controls were enrolled for the study. Bet v 1, Bet v 2, Ole e 1, Der p 1, Der p 2, Der f 1, Der f 2, Pru p 3, tropomyosin were tested both with Immulite™ 2000 and ImmunoCAP™ (Thermo Fisher Scientific, Uppsala, Sweden). Results Sensitivity of allergen‐specific Immunoglobulin E (sIgE) to Ole e 1, Bet v 1, Der p 1, Der p 2, Der f 1, Der f 2, Pen m 1, and Pru p 3 with Immulite™ 2000 was 100%, 100%, 77.1%, 94.3%, 71.4%, 94%, 75%, and 97.1%, respectively, and the specificity was 100% for all the allergens. The overall agreement between Immulite™ 2000 and ImmunoCAP™ (Thermo Fisher Scientific) platforms was 98.6% (Cohen's kappa = 0.979; confidence interval [CI] 95%: 0.960–0.997). From moderate to strong, positive linear correlations between the assays (r2 from 0.322 to 0.860, and Spearman's rho from 0.824 to 0.971) were showed. Conclusions A high diagnostic accuracy of the sIgE to allergen components measurement with Immulite™ 2000 and a high agreement with ImmunoCAP™ platforms were shown in this study.